1995
DOI: 10.1007/bf02740690
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of prenatal cocaine and nicotine exposure on maternal toxicity, postnatal development, and behavior in the rat

Abstract: Two experiments were performed to investigate the interactive effects of prenatal coadministration of cocaine hydrochloride (C) and nicotine tartrate (N). Experiment I was designed to determine doses of C and N that could be coadministered without altering maternal gestational parameters and/or fetal viability. Exposure of Sprague-Dawley rats to combined high-dose C (20 mg/kg) and high-dose N (5.0 mg/kg) on gestation days 8-21 was not more toxic to dam or fetus that that of exposure to C alone. Experiment II i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
3
21
1
1
Order By: Relevance
“…The present findings are consistent with that of Sobrian et al (1995) who found that the same nicotine challenge dose as that used in the present study (1.0 mg/kg) produced a similar increase in total activity and stereotypy regardless of prenatal treatment. However, Shacka et al (1997) found that the same nicotine challenge dose only increased activity in 14-day old male rats prenatally exposed to nicotine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are consistent with that of Sobrian et al (1995) who found that the same nicotine challenge dose as that used in the present study (1.0 mg/kg) produced a similar increase in total activity and stereotypy regardless of prenatal treatment. However, Shacka et al (1997) found that the same nicotine challenge dose only increased activity in 14-day old male rats prenatally exposed to nicotine.…”
Section: Discussionsupporting
confidence: 93%
“…was administered immediately before placement into the activity chamber. The dose was chosen based on prior studies (Shacka et al, 1997;Sobrian et al, 1995). Two pups from each litter (one of each sex) were injected with saline, while the other two pups received nicotine.…”
Section: Nicotine-induced Locomotor Activitymentioning
confidence: 99%
“…It is in agreement with the study of Šlamberová et al ( 2006) showing that M administered during prenatal and/ or preweaning periods alters functional development of rat pups and that it alters two generations of offspring (Šlamberová et al, 2007). There are other studies examining the effect of other stimulant drugs such as amphetamine and cocaine on development of rat pups (Henderson & McMillen, 1990;Sobrian, Ali, Slikker, & Holson, 1995). Study of Henderson and McMillen (1990) demonstrated that the development of righting on surface is delayed in pups, who were prenatally exposed to cocaine (15 mg/kg).…”
Section: Discussionmentioning
confidence: 97%
“…The development of the respiratory rhythm generator must be well established and functionally robust by birth and fetal breathing movements are necessary for the proper maturation of the lungs with compounds which alter respiratory rhythm commonly resulting in lung hypoplasia (Dornan et al 1984, Harding 1995, Kobayashi et al 2001. Notably, while prenatal nicotine exposure has been demonstrated to alter fetal lung development in rats (Maritz and van Wyk 1997) and associated neuronal nAChR expression in primates (Sekhon et al 1999), it paradoxically does not cause neonatal death during normoxic conditions in rats (Geller 1959, Sobrian et al 1995. In a histopathologic examination of GD 21 fetal rat lungs collected following sulfoxafl or maternal exposure no alterations were observed (data not shown).…”
Section: Neuronal Nachrsmentioning
confidence: 99%